60 years of glacier elevation and mass changes in the Maipo River Basin, central Andes of Chile - Farías Barahona, David; Ayala, Álvaro; Bravo, Claudio; Vivero, Sebastián; Seehaus, Thorsten; Vijay, Saurabh; Schaefer, Marius; Buglio, Franco; Casassa, Gino; Braun, Matthias (Remote Sensing, 2020)
Glaciers in the central Andes of Chile are fundamental freshwater sources for ecosystems and communities. Overall, glaciers in this region have shown continuous recession and down-wasting, but long-term glacier mass balance studies providing precise estimates of these changes are scarce. Here, we present the first long-term (1955-2013/2015), region-specific glacier elevation and mass change estimates for the Maipo River Basin, from which the densely populated metropolitan region of Chile obtains most of its freshwater supply. We calculated glacier elevation and mass changes using historical topographic maps, Shuttle Radar Topography Mission (SRTM), TerraSAR-X add-on for Digital Elevation Measurements (TanDEM-X), and airborne Light Detection and Ranging (LiDAR) digital elevation models. The results indicated a mean regional glacier mass balance of-0.12 ± 0.06 m w.e. a-1, with a total mass loss of 2.43 ± 0.26 Gt for the Maipo River Basin between 1955-2013. The most negative glacier mass balance was the Olivares sub-basin, with a mean value of-0.29 ± 0.07mw.e. a-1. We observed spatially heterogeneous glacier elevation and mass changes between 1955 and 2000, and more negative values between 2000 and 2013, with an acceleration in ice thinning rates starting in 2010, which coincides with the severe drought. Our results provide key information to improve glaciological and hydrological projections in a region where water resources are under pressure.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Central Andes; Glacier elevation changes; Glacier mass balance; InSAR; LiDAR; Mountain glaciers

A near 90-year record of the evolution of El Morado Glacier and its proglacial lake, Central Chilean Andes - Farías Barahona, David; Wilson, Ryan; Bravo, Claudio; Vivero, Sebastian; Caro, Alexis; Shaw, Thomas E.; Casassa, Gino; Ayala, Alvaro; Mejias, Alonso; Harrison, Stephan; Glasser, Neil F.; Mcphee, James; et al. (Journal of Glaciology, 2020)
Using an ensemble of close- and long-range remote sensing, lake bathymetry and regional meteorological data, we present a detailed assessment of the geometric changes of El Morado Glacier in the Central Andes of Chile and its adjacent proglacial lake between 1932 and 2019. Overall, the results revealed a period of marked glacier down wasting, with a mean geodetic glacier mass balance of -0.39 +/- 0.15 m w.e.a(-1)observed for the entire glacier between 1955 and 2015 with an area loss of 40% between 1955 and 2019. We estimate an ice elevation change of -1.00 +/- 0.17 m a(-1)for the glacier tongue between 1932 and 2019. The increase in the ice thinning rates and area loss during the last decade is coincident with the severe drought in this region (2010-present), which our minimal surface mass-balance model is able to reproduce. As a result of the glacier changes observed, the proglacial lake increased in area substantially between 1955 and 2019, with bathymetry data suggesting a water volume of 3.6 million m(3)in 2017. This study highlights the need for further monitoring of glacierised areas in the Central Andes. Such efforts would facilitate a better understanding of the downstream impacts of glacier downwasting.
CRIS-Team WoS Importer:2020-10-16

Assessing Snow Accumulation Patterns and Changes on the Patagonian Icefields - Bravo, Claudio; Bozkurt, Deniz; Gonzalez-Reyes, Alvaro; Quincey, Duncan J.; Ross, Andrew N.; Farías Barahona, David; Rojas, Maisa (Frontiers in Environmental Science, 2019)
Recent evidence shows that most Patagonian glaciers are receding rapidly. Due to the lack of in situ long-term meteorological observations, the understanding of how glaciers are responding to changes in climate over this region is extremely limited, and uncertainties exist in the glacier surface mass balance model parameterizations. This precludes a robust assessment of glacier response to current and projected climate change. An issue of central concern is the accurate estimation of precipitation phase. In this work, we have assessed spatial and temporal patterns in snow accumulation in both the North Patagonia Icefield (NPI) and South Patagonia Icefield (SPI). We used a regional climate model, RegCM4.6 and four Phase Partitioning Methods (PPM) in addition to short-term snow accumulation observations using ultrasonic depth gauges (UDG). Snow accumulation shows that rates are higher on the west side relative to the east side for both icefields. The values depend on the PPM used and reach a mean difference of 1,500 mm w.e., with some areas reaching differences higher than 3,500 mm w.e. These differences could lead to divergent mass balance estimations depending on the scheme used to define the snow accumulation. Good agreement is found in comparing UDG observations with modeled data on the plateau area of the SPI during a short time period; however, there are important differences between rates of snow accumulation determined in this work and previous estimations using ice core data at annual scale. Significant positive trends are mainly present in the autumn season on the west side of the SPI, while on the east side, significant negative trends in autumn were observed. Overall, for the rest of the area and during other seasons, no significant changes can be determined. In addition, glaciers with positive and stable elevation and frontal changes determined by previous works are related to areas where snow accumulation has increased during the period 2000-2015. This suggests that increases in snow accumulation are attenuating the response of some Patagonian glaciers to warming in a regional context of overall glacier retreat.
CRIS-Team WoS Importer:2019-04-18

Constraining glacier elevation and mass changes in South America - Braun, Matthias; Malz, Philipp; Sommer, Christian; Farías Barahona, David; Sauter, Tobias; Casassa, Gino; Soruco, Alvaro; Skvarca, Pedro; Seehaus, Thorsten (Nature Climate Change, 2019)
Excluding the large ice sheets of Greenland and Antarctica, glaciers in South America are large contributors to sea-level rise<a title="Marzeion, B., Kaser, G., Maussion, F. & Champollion, N. Limited influence of climate change mitigation on short-term glacier mass loss. Nat. Clim. Change 8, 305–308 (2018)." href="https://www.nature.com/articles/s41558-018-0375-7#ref-CR1">1. Their rates of mass loss, however, are poorly known. Here, using repeat bi-static synthetic aperture radar interferometry over the years 2000 to 2011/2015, we compute continent-wide, glacier-specific elevation and mass changes for 85% of the glacierized area of South America. Mass loss rate is calculated to be 19.43 ± 0.60 Gt a−1 from elevation changes above ground, sea or lake level, with an additional 3.06 ± 1.24 Gt a−1 from subaqueous ice mass loss not contributing to sea-level rise. The largest contributions come from the Patagonian icefields, where 83% mass loss occurs, largely from dynamic adjustments of large glaciers. These changes contribute 0.054 ± 0.002 mm a−1 to sea-level rise. In comparison with previous studies2, tropical and out-tropical glaciers — as well as those in Tierra del Fuego — show considerably less ice loss. These results provide basic information to calibrate and validate glacier-climate models and also for decision-makers in water resource management3</sup
Keywords: SAR; Interferometry; glacier elevation change; glacier mass balance; TanDEM-X; SRTM; Andes; South America; Patagonia; geodetic

Continent wide monitoring of glacier surface elevation changes and glacer mass balances - Seehaus, Thorsten; Malz, Philipp; Sommer, Christian; Farías Barahona, David; Braun, Matthias (Proceedings of 2019 Big Data from Space, 2019)

Detailed quantification of glacier elevation and mass changes in South Georgia - Farías Barahona, David; Sommer, Christian; Sauter, Tobias; Bannister, Daniel; Seehaus, Thorsten; Malz, Philipp; Casassa, Gino; Mayewski, Paul A.; Turton, Jenny; Braun, Matthias (Environmental Research Letters, 2020)

Geodetic Mass Balances and Area Changes of Echaurren Norte Glacier (Central Andes, Chile) between 1955 and 2015 - Farías Barahona, David; Vivero, Sebastián; Casassa, Gino; Schaefer, Marius; Burger, Flavia; Seehaus, Thorsten; Iribarren-Anacona, Pablo; Escobar, Fernando; Braun, Matthias (Remote Sensing, 2019)
The Echaurren Norte Glacier is a reference glacier for the World Glacier Monitoring Service (WGMS) network and has the longest time series of glacier mass balance data in the Southern Hemisphere. The data has been obtained by the direct glaciological method since 1975. In this study, we calculated glacier area changes using satellite images and historical aerial photographs, as well as geodetic mass balances for different periods between 1955 and 2015 for the Echaurren Norte Glacier in the Central Andes of Chile. Over this period, this glacier lost 65% of its original area and disaggregated into two ice bodies in the late 1990s. The geodetic mass balances were calculated by differencing digital elevation models derived from several sources. The results indicated a mean cumulative glacier wide mass loss of −40.64 ± 5.19 m w.e. (−0.68 ± 0.09 m w.e. a−1). Within this overall downwasting trend, a positive mass balance of 0.54 ± 0.40 m w.e. a−1 was detected for the period 2000–2009. These estimates agree with the results obtained with the glaciological method during the same time span. Highly negative mass change rates were found from 2010 onwards, with −1.20 ± 0.09 m w.e. a−1 during an unprecedented drought in Central Andes of Chile. The observed area and the elevation changes indicate that the Echaurren Norte Glacier may disappear in the coming years if negative mass balance rates prevai
Keywords: glacier mass balance; geodetic method; LiDAR; central Andes; glacier mapping; mountain glacier

Glacier albedo reduction and drought effects in the extratropical Andes, 1986-2020 - Shaw, Thomas E.; Ulloa, Genesis; Farías Barahona, David; Fernandez, Rodrigo; Lattus, Jose M.; McPhee, James (Journal of Glaciology, 2021)
Surface albedo typically dominates the mass balance of mountain glaciers, though long-Term trends and patterns of glacier albedo are seldom explored. We calculated broadband shortwave albedo for glaciers in the central Chilean Andes (33-34°S) using end-of-summer Landsat scenes between 1986 and 2020. We found a high inter-Annual variability of glacier-wide albedo that is largely a function of the glacier fractional snow-covered area and the total precipitation of the preceding hydrological year (up to 69% of the inter-Annual variance explained). Under the 2010-2020 'Mega Drought' period, the mean albedo, regionally averaged ranging from 0.25-0.5, decreased by-0.05 on average relative to 1986-2009, with the greatest reduction occurring 3500-5000 m a.s.l. In 2020, differences relative to 1986-2009 were-0.14 on average as a result of near-complete absence of late summer snow cover and the driest hydrological year since the Landsat observation period began (90% reduction of annual precipitation relative to the 1986-2009 period). We found statistically significant, negative trends in glacier ice albedo of up to-0.03 per decade, a trend that would have serious implications for the future water security of the region, because glacier ice melt acts to buffer streamflow shortages under severe drought conditions.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Albedo; Andes; climate; drought; glacier; remote sensing

Glacier protection laws: Potential conflicts in managing glacial hazards and adapting to climate change - Iribarren-Anacona, Pablo; Kinney, Josie; Schaefer, Marius; Harrison, Stephan; Wilson, Ryan; Segovia, Alexis; Mazzorana, Bruno; Guerra, Felipe; Farías Barahona, David; Reynolds, John; Glasser, Neil (Ambio, 2018)
The environmental, socioeconomic and cultural significance of glaciers has motivated several countries to regulate activities on glaciers and glacierized surroundings. However, laws written to specifically protect mountain glaciers have only recently been considered within national political agendas. Glacier Protection Laws (GPLs) originate in countries where mining has damaged glaciers and have been adopted with the aim of protecting the cryosphere from harmful activities. Here, we analyze GPLs in Argentina (approved) and Chile (under discussion) to identify potential environmental conflicts arising from law restrictions and omissions. We conclude that GPLs overlook the dynamics of glaciers and could prevent or delay actions needed to mitigate glacial hazards (e.g. artificial drainage of glacial lakes) thus placing populations at risk. Furthermore, GPL restrictions could hinder strategies (e.g. use of glacial lakes as reservoirs) to mitigate adverse impacts of climate change. Arguably, more flexible GPLs are needed to protect us from the changing cryosphere.<br

Glacier runoff variations since 1955 in the Maipo River basin, in the semiarid Andes of central Chile - Ayala, Alvaro; Farías Barahona, David; Huss, Matthias; Pellicciotti, Francesca; Mcphee, James; Farinotti, Daniel (Cryosphere, 2020)
As glaciers adjust their size in response to climate variations, long-term changes in meltwater production can be expected, affecting the local availability of water resources. We investigate glacier runoff in the period 1955-2016 in the Maipo River basin (4843 km(2), 33.0-34.3 degrees S, 69.8-70.5 degrees W), in the semiarid Andes of Chile. The basin contains more than 800 glaciers, which cover 378 km(2) in total (inventoried in 2000). We model the mass balance and runoff contribution of 26 glaciers with the physically oriented and fully distributed TOPKAPI (Topographic Kinematic Approximation and Integration)-ETH glacio-hydrological model and extrapolate the results to the entire basin. TOPKAPI-ETH is run at a daily time step using several glaciological and meteorological datasets, and its results are evaluated against streamflow records, remotely sensed snow cover, and geodetic mass balances for the periods 1955-2000 and 2000-2013. Results show that in 1955-2016 glacier mass balance had a general decreasing trend as a basin average but also had differences between the main sub-catchments. Glacier volume decreased by one-fifth (from 18.6 +/- 4.5 to 14.9 +/- 2.9 km(3)). Runoff from the initially glacierized areas was 177 +/- 25 mm yr(-1) (16 +/- 7 % of the total contributions to the basin), but it shows a decreasing sequence of maxima, which can be linked to the interplay between a decrease in precipitation since the 1980s and the reduction of ice melt. Glaciers in the Maipo River basin will continue retreating because they are not in equilibrium with the current climate. In a hypothetical constant climate scenario, glacier volume would reduce to 81 +/- 38 % of the year 2000 volume, and glacier runoff would be 78 +/- 30 % of the 1955-2016 average. This would considerably decrease the drought mitigation capacity of the basin.
CRIS-Team WoS Importer:2020-07-17

Interannual variability in glacier contribution to runoff from a high-elevation Andean catchment: understanding the role of debris cover in glacier hydrology - Burger, Flavia; Ayala, Alvaro; Farías Barahona, David; Shaw, Thomas E.; Macdonell, Shelley; Brock, Ben; Mcphee, James; Pellicciotti, Francesca (Hydrological Processes, 2019)
We present a field-data rich modelling analysis to reconstruct the climatic forcing, glacier response, and runoff generation from a high-elevation catchment in central Chile over the period 2000–2015 to provide insights into the differing contributions of debris-covered and debris-free glaciers under current and future changing climatic conditions. Model simulations with the physically based glacio-hydrological model TOPKAPI-ETH reveal a period of neutral or slightly positive mass balance between 2000 and 2010, followed by a transition to increasingly large annual mass losses, associated with a recent mega drought. Mass losses commence earlier, and are more severe, for a heavily debris-covered glacier, most likely due to its strong dependence on snow avalanche accumulation, which has declined in recent years. Catchment runoff shows a marked decreasing trend over the study period, but with high interannual variability directly linked to winter snow accumulation, and high contribution from ice melt in dry periods and drought conditions. The study demonstrates the importance of incorporating local-scale processes such as snow avalanche accumulation and spatially variable debris thickness, in understanding the responses of different glacier types to climate change. We highlight the increased dependency of runoff from high Andean catchments on the diminishing resource of glacier ice during dry years.
CRIS-Team Scopus Importer:2019-05-07
Keywords: debris-covered glaciers; dry Andes of Chile; glacier mass balance; glacier runoff; glacio-hydrological modelling

Strategies for regional modeling of surface mass balance at the Monte Sarmiento Massif, Tierra del Fuego - Temme, Franziska; Farías Barahona, David; Seehaus, Thorsten; Janã, Ricardo; Arigony-Neto, Jorge; Gonzalez, Inti; Arndt, Anselm; Sauter, Tobias; Schneider, Christoph; Fürst, Johannes (Cryosphere, 2023)
This study investigates strategies for calibration of surface mass balance (SMB) models in the Monte Sarmiento Massif (MSM), Tierra del Fuego, with the goal to achieve realistic simulations of the regional SMB. Applied calibration strategies range from a local single-glacier calibration to a regional calibration with the inclusion of a snowdrift parametrization. We apply four SMB models of different complexity. This way, we examine the model transferability in space, the benefit of regional mass change observations and the advantage of increasing the complexity level regarding included processes. Measurements include ablation and ice thickness observations at Schiaparelli Glacier as well as elevation changes and flow velocity from satellite data for the entire study site. Performance of simulated SMB is validated against geodetic mass changes and stake observations of surface melting. Results show that transferring SMB models in space is a challenge, and common practices can produce distinctly biased estimates. Model performance can be significantly improved by the use of remotely sensed regional observations. Furthermore, we have shown that snowdrift does play an important role for the SMB in the Cordillera Darwin, where strong and consistent winds prevail. The massif-wide average annual SMB between 2000 and 2022 falls between -0.28 and -0.07 m w.e. yr-1, depending on the applied model. The SMB is mainly controlled by surface melting and snowfall. The model intercomparison does not indicate one obviously best-suited model for SMB simulations in the MSM.<br

Surface energy fluxes on Chilean glaciers: measurements and models - Schaefer, Marius; Fonseca-Gallardo, Duilio; Farías Barahona, David; Casassa, Gino (Cryosphere, 2020)
The surface energy fluxes of glaciers determine surface melt, and their adequate parametrization is one of the keys to a successful prediction of future glacier mass balance and freshwater discharge. Chile hosts glaciers in a large range of latitudes under contrasting climatic settings: from 18 degrees S in the Atacama Desert to 55 degrees S on Tierra del Fuego. Using three different methods, we computed surface energy fluxes for five glaciers which represent the main glaciological zones of Chile. We found the main energy sources for surface melt change from the Central Andes, where the net shortwave radiation is driving the melt, to Patagonia, where the turbulent fluxes are an important source of energy. We inferred higher surface melt rates for Patagonian glaciers as compared to the glaciers of the Central Andes due to a higher contribution of the turbulent sensible heat flux, less negative net longwave radiation and a positive contribution of the turbulent latent heat flux. The variability in the atmospheric emissivity was high and not able to be explained exclusively by the variability in the inferred cloud cover. The influence of the stability correction and the roughness length on the magnitude of the turbulent fluxes in the different climate settings was examined. We conclude that, when working towards physical melt models, it is not sufficient to use the observed melt as a measure of model performance; the model parametrizations of individual components of the energy balance have to be validated individually against measurements.
CRIS-Team WoS Importer:2020-09-11

The foundations of the Patagonian icefields - Fürst, Johannes; Farías Barahona, David; Blindow, Norbert; Casassa, Gino; Gacitúa, Guisella; Koppes, Michèle; Lodolo, Emanuele; Millan, Romain; Minowa, Masahiro; Mouginot, Jérémie; Pȩtlicki, Michał; Rignot, Eric; et al. (Communications Earth & Environment, 2024)
The two vast Patagonian icefields are a global hotspot for ice-loss. However, not much is known about the total ice volume they store - let alone its spatial distribution. One reason is that the abundant record of direct thickness measurements has never been systematically exploited. Here, this record is combined with remotely-sensed information on past ice thickness mapped from glacier retreat. Both datasets are incorporated in a state-of-the-art, mass-conservation approach to produce a well-informed map of the basal topography beneath the icefields. Its major asset is the reliability increase of thicknesses values along the many marine- and lake-terminating glaciers. For these, frontal ice-discharge is notably lower than previously reported. This finding implies that direct climatic control was more influential for past ice loss. We redact a total volume for both icefields in 2000 of 5351 km3. Despite the wealth of observations used in this assessment, relative volume uncertainties remain elevated.
CRIS-Team Scopus Importer:2024-03-29